2023
DOI: 10.3390/nu15020388
|View full text |Cite
|
Sign up to set email alerts
|

Five Days of Tart Cherry Supplementation Improves Exercise Performance in Normobaric Hypoxia

Abstract: Previous studies have shown tart cherry (TC) to improve exercise performance in normoxia. The effect of TC on hypoxic exercise performance is unknown. This study investigated the effects of 5 days of tart cherry (TC) or placebo (PL) supplementation on hypoxic exercise performance. Thirteen healthy participants completed an incremental cycle exercise test to exhaustion (TTE) under two conditions: (i) hypoxia (13% O2) with PL and (ii) hypoxia with TC (200 mg anthocyanin per day for 4 days and 100 mg on day 5). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…This study investigated the effects of 2 weeks of mango ingestion on moderating exerciseinduced inflammation in a randomized crossover trial with 22 male and female cyclists. The influence of 2-4 weeks' intake of fruit carbohydrates and polyphenols on inflammation resolution following exercise stress is an emerging area of scientific endeavor [1][2][3][4][5][6]8]. The findings from this study indicated that 2 weeks of mango ingestion did not mitigate plasma oxylipin levels after 2.25 h of intensive cycling.…”
Section: Introductionmentioning
confidence: 60%
“…This study investigated the effects of 2 weeks of mango ingestion on moderating exerciseinduced inflammation in a randomized crossover trial with 22 male and female cyclists. The influence of 2-4 weeks' intake of fruit carbohydrates and polyphenols on inflammation resolution following exercise stress is an emerging area of scientific endeavor [1][2][3][4][5][6]8]. The findings from this study indicated that 2 weeks of mango ingestion did not mitigate plasma oxylipin levels after 2.25 h of intensive cycling.…”
Section: Introductionmentioning
confidence: 60%
“…Intensive exercise training induces physiological stress, including inflammation, oxidative stress, and transient immune dysfunction. Our research group and others have investigated nutrition-based approaches, including increased intake of fruits and polyphenols as countermeasures to these exercise-induced indicators of metabolic stress [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. We have focused on the use of multi-omics methods (i.e., lipidomics, metabolomics, proteomics, genomics, and epigenetics) to capture the complex biochemical interactions that occur in these types of sports nutrition investigations [ 4 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the effects of 2 weeks of mango ingestion on moderating exercise-induced inflammation in a randomized crossover trial with 22 male and female cyclists. The influence of 2–4 weeks’ intake of fruit carbohydrates and polyphenols on inflammation resolution following exercise stress is an emerging area of scientific endeavor [ 1 , 2 , 3 , 4 , 5 , 6 , 8 ]. The findings from this study indicated that 2 weeks of mango ingestion did not mitigate plasma oxylipin levels after 2.25 h of intensive cycling.…”
Section: Introductionmentioning
confidence: 99%